Studi Deskriptif Mengenai Frekuensi Menonton Televisi dan Main Game Elektronik pada Anak di Semarang - Desiningrum, Dinie Ratri; Prihatsanti, Unika (Universitas Muria Kudus, 2011)
Not all mass media content beneficial to audiences. Children are the most vulnerable group of viewers with the negative impact from television and technological advances of the internet and video games. This study aims to capture the data in the form frequency of watching television and playing electronic games on children in Semarang.The spread of datas were done by using two questionnaires, namely the frequency of watching television and playing electronic games. Sampling technique was used in incidental technique. The research method used was quantitative and the results were analyzed with descriptive statistics. The study found that most children in Semarang watching television and playing electronic games for more than 2 (two) hours per day, while the government recommends consumption of televisions and other electronic audiovisual media is a maximum of two hours each day, under parental guidance. This study is one fact which indicates that the alert of television and electronic games has not been noticed by parents, then it is further expected that research about the negative impact of television and electronic games.